Sistem Informasi Pemesanan dan Peningkatan Promosi pada Toko Thytashop - Nengsianti Merratte; Pujianti Wahyuningsih; Ririn Indraswari; Mursalim Sawawi; Syarifah Fitra Ramdhani (Ikatan Ahli Informatika Indonesia, 2023)
Thytashop is a shop that sells traditional Toraja clothing, which is located on the Toraja-Mamasa axis road, precisely in Belau, Masanda subdistrict, Tana Toraja district. The ordering system at Thytashop is not yet computerized, so it still uses a manual system. The promotion system also only uses social media, namely Facebook and confirms orders via WhatsApp. Bookkeeping and transactions are still physical which can result in data being vulnerable to problems such as being damaged or scattered. The features built by researchers are promotional and best seller features in order to increase consumer attraction when visiting Thytashop stores. The system design used in this research is Unified Modeling Language (UML), which consists of use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The database management uses mysql php myadmin and then this system will be built using the Hypertext Preprocessor (PHP) programming language. The result of this research is the creation of an information system website built for placing orders, transactions as well as promotional media which is expected to make it easier for business owners and managers to provide better service to customers